Preparedness of Primary Health Care Leaders During COVID-19 Outbreak, Riyadh, Saudi Arabia: A Qualitative Study - Alakeely M; Almutari A; Masud D; Altulaihi B (Dove Medical Press, 2021)
Maha Alakeely,1,2 Arwa Almutari,2,3 Nazish Masud,2,4 Bader Altulaihi1,2 1Department of Family Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Centre, Riyadh, Saudi Arabia; 3Department of Radiology, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 4Research Unit, Department of Medical Education, College of Medicine, King Saud BIN Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Maha AlakeelyDepartment of Family Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi ArabiaEmail Mahaakeely@gmail.comPurpose: Our study aims to explore the preparedness of the frontline leaders of the primary health care (PHC) centres in dealing with the COVID-19 pandemic and to understand their experiences in implementing preventive interventions necessary to routinise health care service delivery.Methods: A qualitative exploratory study was conducted using in-depth interviews with the participants in English. The interviews were transcribed verbatim, and inductive coding followed by thematic analysis was performed using NVivo version 12.Participants: Six participants in charge of managing their respective primary health care settings were included in the study. Purposive sampling was used to identify participants until saturation was reached. After agreement, the interviews were scheduled as per availability.Results: The results were grouped into three major themes and nine subthemes. Most leaders reported that they were trained in pandemic preparedness, but there was a lack of focused readiness to handle a massive-scale, infectious disease outbreak or pandemic. The initial lack of guidelines specific to COVID-19 was a barrier in making decisions related to staff and patient care. Services were interrupted initially and there was lack of staff since many acquired COVID-19 and were isolated. The shortage of the staff was delt by repurposing staff from other departments to the essential care services. Fears related to pandemic was one of the main concerns reported among staff and patients. Several initiatives were taken to ensure staff safety and uninterrupted service delivery to patients. The use of technology was an effective mechanism in preparing for the pandemic.Conclusion: This qualitative study helped in understanding the experiences of primary health care leaders during the COVID-19 pandemic. The facilities lacked overall preparedness at the beginning of the pandemic; however, many initiatives were taken in course of time to ensure smooth operations and continued service delivery to the patients.Keywords: COVID-19, preparedness, primary health care centre, PHC, Saudi Arabia, prevention